Transient Thermal Elastohydrodynamic Modeling of Cam–Follower Systems: Understanding Performance. Issue 4 (3rd July 2016) - Raisin, Jonathan; Fillot, Nicolas; Vergne, Philippe; Dureisseix, David; Lacour, Vincent
ABSTRACT: This article deals with the lubrication of cam–follower contacts in automobile racing applications. Time-dependent thermal elastohydrodynamic line contact simulations are performed to analyze the contact performance achieved with a shear-thinning lubricant under highly dynamic conditions. Comparisons between different simulations are used to quantify the respective influence of shear thinning, thermal softening, and transient effects on friction and film thickness. Furthermore, this article highlights the formation and transport of a transient dimple responsible for an increase in lift close to the conditions where reversals of entrainment occur. Temperature distributions across the film thickness and pressure variations are reported to discuss the underlying phenomena.